Providing Task Instructions During Motor Training Enhances Performance and Modulates Attentional Brain Networks - Penalver-Andres, Joaquin; Buetler, Karin A.; Koenig, Thomas; Müri, René Martin; Marchal-Crespo, Laura (Frontiers in Neuroscience, 2021)
Learning a new motor task is a complex cognitive and motor process. Especially early during motor learning, cognitive functions such as attentional engagement are essential, e.g., to discover relevant visual stimuli. Drawing participant's attention towards task-relevant stimuli – e.g., with task instructions using visual cues or explicit written information – is a common practice to support cognitive engagement during training and, hence, accelerate motor learning. However, there is little scientific evidence about how visually cued or written task instructions affect attentional brain networks during motor learning. In this experiment (https://clinicaltrials.gov/ct2/show/NCT04759976), we trained 36 healthy participants in a virtual motor task: surfing waves by steering a boat with a joystick. We measured the participants' motor performance and observed attentional brain networks using alpha-band electroencephalographic (EEG) activity before and after training. Participants received one of the following task instructions during training: 1) No explicit task instructions and letting participants surf freely (implicit training; IMP); 2) Task instructions provided through explicit visual cues (explicit-implicit training; E-IMP); or 3) through explicit written commands (explicit training; E). We found that providing task instructions during training (E and E-IMP) resulted in less post-training motor variability – linked to enhanced performance – compared to training without instructions (IMP). After training, participants trained with visual cues (E-IMP) enhanced the alpha-band strength over parieto-occipital and frontal brain areas at wave onset. In contrast, participants who trained with explicit commands (E) showed decreased fronto-temporal alpha activity. Thus, providing task instructions in written (E) or using visual cues (E-IMP) leads to similar motor performance improvements by enhancing activation on different attentional networks. While training with visual cues (E-IMP) may be associated with visuo-attentional processes, verbal-analytical processes may be more prominent when written explicit commands are provided (E). Together, we suggest that training parameters such as task instructions modulate the attentional networks observed during motor practice and may support participant's cognitive engagement, compared to training without instructions.